050. Surviving Multiple Traumas: A 37-Year-Old Male with Gunshot-Induced Hematopneumothorax and Hollow Organ Perforation - Manik, David Restu P.; Muhar, Adi Muradi (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p050, 2024)
Background : Traumatic gunshot wounds to the chest and abdomen pose significant challenges in emergency surgical management. This case report presents the rapid diagnosis and successful treatment of a 37-year-old male who sustained gunshot wounds to the chest and abdomen, leading to hematopneumothorax and hollow organ perforation. Case: The patient, a 37-year-old male, was admitted to Adam Malik Hospital with shortness of breath and severe abdominal pain following a gunshot injury to the chest and lower abdomen. On primary survey, the patient exhibited tachypnea (RR 26 tpm) and hypoxia (SpO2 94% on room air), which improved with oxygen therapy. Vital signs were stable, but a left-sided hematopneumothorax and abdominal tenderness suggested hollow organ perforation. Radiological and FAST ultrasound findings confirmed the diagnosis. Emergency chest tube insertion and exploratory laparotomy were performed. The chest tube revealed hemorrhagic effusion, and laparotomy identified two small bowel perforations at 100 cm and 130 cm from the ligament of Treitz, alongside an impaled object in the mesentery. Primary suturing of the perforations was performed, and the abdomen was irrigated thoroughly. Postoperative recovery was uneventful, with the patient showing rapid clinical improvement. Conclusion: Rapid emergency surgical response led to a favorable outcome in a patient with life-threatening thoracoabdominal gunshot wounds, emphasizing the role of timely interventions in trauma care.